A layered heterostructure tungsten-copper composite material and a method for preparing the same

By using rapid sintering and lamination techniques to prepare ultrafine/nanostructured layered heterogeneous tungsten-copper composites, the inverse relationship between mechanical and electrical conductivity properties of tungsten-copper composites was resolved, reducing preparation costs and improving electrical conductivity and wear resistance.

CN119502530BActive Publication Date: 2026-11-06BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411673952.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2026-11-06
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Existing tungsten-copper composites exhibit an inverse relationship between mechanical properties and electrical conductivity. Furthermore, layered tungsten-copper composites have high preparation costs, and their electrical conductivity and wear resistance need improvement. The thickness of the tungsten foil also limits further performance enhancement.

Method used

A rapid sintering technique was used to prepare ultrafine/nanostructured tungsten-copper composite sheets. The sheets were cut into thin sheets by wire cutting and then stacked alternately. The sheets were cleaned with sodium hydroxide solution and dilute hydrochloric acid solution, and finally sintered under high temperature and high pressure to form a layered heterostructure, which can replace the traditional tungsten foil preparation method.

Benefits of technology

It significantly improves the strength, conductivity, and wear resistance of layered heterostructure tungsten-copper composite materials, reduces preparation costs, forms a more stable oxide lubricating film, and enhances overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005146587900000011
    Figure HDA0005146587900000011
  • Figure HDA0005146587900000012
    Figure HDA0005146587900000012
  • Figure HDA0005146587900000021
    Figure HDA0005146587900000021
Patent Text Reader

Abstract

The application discloses a layered heterostructure tungsten-copper composite material and a preparation method thereof, and belongs to the field of powder metallurgy. The layered heterostructure tungsten-copper composite material is formed by alternately distributing an ultra-fine / nano-structure high-tungsten-content tungsten-copper layer and an ultra-fine / nano-structure low-tungsten-content tungsten-copper layer or a copper layer, and is formed by slicing an ultra-fine / nano tungsten-copper composite material, and then stacking and sintering. Due to the strengthening effect of the ultra-fine / nano structure and the unique stress distribution and current density distribution in the bearing process caused by the uneven distribution of the tungsten phase, the layered heterostructure tungsten-copper composite material has higher compressive strength, electrical conductivity and wear resistance than other tungsten-copper composite materials, including a tungsten-copper layered tungsten-copper composite material formed by stacking and sintering pure tungsten sheets and pure copper sheets and a homogeneous structure tungsten-copper composite material with the same composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of powder metallurgy, and specifically relates to a layered heterostructure tungsten-copper composite material with high comprehensive performance and its preparation method. Background Technology

[0002] Due to their excellent comprehensive properties such as high strength, high conductivity, wear resistance, and ablation resistance, tungsten-copper composites are widely used in electrical contacts, EDM electrodes, and other fields. Generally, tungsten-copper composites are prepared by powder metallurgy, exhibiting a microstructure with uniformly distributed tungsten and copper. For this type of tungsten-copper composite, the properties are affected by grain size and composition as follows: coarse-grained tungsten-copper composites have good conductivity but lower strength and wear resistance; ultrafine / nano-structured tungsten-copper composites have high strength and good wear resistance, but lower conductivity; adding alloying elements or a second phase can strengthen tungsten-copper composites, but it will also reduce their conductivity. Therefore, the mechanical properties and conductivity of tungsten-copper composites exhibit an inverse relationship, limiting their service performance.

[0003] In addition, tungsten-copper composites can also be prepared by laminating and sintering tungsten foil and copper foil. For example, patents CN202111578364.4 and CN202210358124.1 disclose methods for preparing layered tungsten-copper composites using pure tungsten foil as raw material. According to relevant research (Sun et al., Composites Part B, 2024, 283: 111641), layered tungsten-copper composites show significantly improved strength, electrical conductivity, and wear resistance parallel to the lamellar direction compared to coarse-grained tungsten-copper composites with a uniform structure. However, due to technological limitations, the thickness of tungsten foil is generally in the hundreds of micrometers, resulting in a large tungsten layer thickness in the prepared layered tungsten-copper composite material, which limits further improvement in its mechanical properties. At the same time, due to the high density of dislocations inside the tungsten foil and the interface problems between the tungsten and copper layers, the electrical conductivity of this layered tungsten-copper composite material still has a certain gap from the theoretical value. Although this layered tungsten-copper composite material exhibits higher wear resistance, the large layer thickness also prevents the formation of a stable and continuous oxide lubricating film on the surface during wear, leaving considerable room for improvement in its wear resistance. Finally, the complex rolling process of tungsten foil increases the preparation cost of tungsten foil, resulting in a higher preparation cost for this layered tungsten-copper composite material. Summary of the Invention

[0004] To address the aforementioned issues, this invention proposes a layered heterogeneous structure design scheme and preparation method for tungsten-copper composite materials. The tungsten-copper composite materials prepared by this method exhibit significantly improved compressive strength, electrical conductivity, and wear resistance compared to existing homogeneous tungsten-copper composite materials and layered tungsten-copper composite materials.

[0005] The technical solution of the present invention is as follows:

[0006] A layered heterostructure tungsten-copper composite material and its preparation method, characterized by comprising the following steps:

[0007] (a) High-density tungsten copper composite material with ultrafine or nanocrystalline structure with high tungsten content (named A) and low-tungsten content tungsten copper composite material or pure copper (named B) were prepared by sintering using rapid sintering technology.

[0008] (b) Two tungsten copper composite materials were cut into thin sheets of the same size and specific thickness using wire cutting, which were named foil A and foil B respectively. Foil B could also be made directly from copper foil. Foil A and foil B were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides from their surfaces.

[0009] (c) Foil A and foil B are alternately stacked and placed in a mold, and rapidly sintered under a certain temperature and pressure to prepare the layered heterostructure tungsten-copper composite material of the present invention.

[0010] In step (a), the tungsten phase grain size in the ultrafine or nanocrystalline tungsten-copper composite material is 50-500 nanometers, the copper content of the tungsten-copper composite material corresponding to A is 10%-40% by mass, and the copper content of the tungsten-copper composite material corresponding to B is 60%-100% by mass.

[0011] In step (b), the thickness of the tungsten-copper composite material sheet cut by wire cutting is 50-500 micrometers, and when B uses pure copper foil, the thickness of the B foil is 10-500 micrometers.

[0012] In step (c), foil A and foil B are stacked alternately, and the specific number of alternating layers is adjusted as needed; the sintering temperature is 700-950 degrees Celsius, the pressure is 50-200 MPa, and the sintering time is 10-60 minutes. The prepared layered heterostructure tungsten-copper composite material exhibits a non-uniform layered structure with alternating tungsten-rich layers and tungsten-poor layers (or pure copper layers), and the grain size of the tungsten phase is between 50-500 nanometers.

[0013] Compared with the prior art, the beneficial effects of the present invention are:

[0014] 1. Compared with layered tungsten-copper composites prepared from tungsten foil, the layered heterostructured tungsten-copper composite material prepared in this invention replaces the tungsten layer with a tungsten-copper layer having an ultrafine / nanostructure. On the one hand, the preparation cost of the ultrafine / nanostructured tungsten-copper layer is lower than that of tungsten foil; on the other hand, the ultrafine / nanostructured tungsten-copper layer has strength comparable to or even higher than that of tungsten foil, as well as higher conductivity. This results in the layered heterostructured tungsten-copper composite material prepared in this invention having higher strength and conductivity than layered tungsten-copper composites prepared from tungsten foil.

[0015] 2. When subjected to wear, a more uniform and stable oxide lubricating film will form on the surface of the A layer (ultrafine / nano-sized tungsten copper layer) in the layered heterostructure tungsten copper composite material prepared by the present invention, thereby reducing the friction coefficient of the tungsten copper composite material. Finally, the layered heterostructure tungsten copper composite material prepared by the present invention exhibits a lower wear rate than the layered tungsten copper composite material prepared using tungsten foil as raw material.

[0016] 3. Compared with traditional uniform tungsten-copper composite materials, the layered heterostructure tungsten-copper composite material prepared by this invention is actually a novel tungsten-copper composite material with non-uniform tungsten phase distribution. The non-uniform distribution of the tungsten phase changes its stress distribution and electron transport path under load, making the layered heterostructure tungsten-copper composite material have higher strength, wear resistance and conductivity than the uniform structure tungsten-copper composite material. Attached Figure Description

[0017] Figure 1 The SEM morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of this invention;

[0018] Figure 2 This is a comparison chart of the compressive strength and electrical conductivity of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of the present invention with other tungsten-copper composite materials;

[0019] Figure 3 This is a comparison chart of the wear rate of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 1 of the present invention and other tungsten-copper composite materials.

[0020] Figure 4 The SEM morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in Example 2 of this invention;

[0021] Figure 5 The image shows the SEM morphology of the (W-20Cu) / (W-90Cu) layered heterostructure tungsten-copper composite material prepared in Example 3 of this invention.

[0022] Figure 2 and Figure 3In this context, "heterogeneous layered tungsten copper" refers to the technical solution of this invention; "tungsten foil preparation of layered tungsten copper" refers to a layered tungsten copper composite material prepared by sintering commercial tungsten foil and copper foil, with tungsten foil thickness and copper foil thickness of 100 micrometers and 50 micrometers, respectively, having the same layered structure as Example 1; "coarse-grained tungsten copper" refers to a commercial W-20Cu composite material prepared by melt infiltration method; and "uniform nanostructured tungsten copper" refers to a nanostructured tungsten copper composite material with the same tungsten phase size and the same copper content as Example 1, with the tungsten phase being uniformly distributed. Detailed Implementation

[0023] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. The embodiments are only examples to help understand the present invention and should not be used as a basis for limiting the present invention.

[0024] Example 1

[0025] (a) Nano W-20Cu powder was prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material bulk with uniform nanocrystalline structure was prepared by rapid sintering technology (A);

[0026] (b) The W-20Cu composite material (A) with a uniform nanocrystalline structure was cut into a 100-micrometer-thick sheet (A foil, 20 mm in diameter) using wire cutting; at the same time, a 50-micrometer-thick pure copper sheet was cut into a sheet with the same diameter as A foil (B foil, 20 mm in diameter) using wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides from their surfaces.

[0027] (c) Stack A foil and B foil alternately (13 layers of A foil and 12 layers of B foil, the specific number can be adjusted as needed), place them in a mold, and sinter rapidly at 900 degrees Celsius and 100 MPa for 20 minutes to prepare (W-20Cu) / Cu layered heterostructure tungsten copper composite material.

[0028] The scanning morphology of the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material prepared in this embodiment is as follows: Figure 1 As shown, its compressive strength reaches 1200 MPa (according to GB / T 228.1, the pressure direction is parallel to the lamellar direction), its electrical conductivity is 50% IACS (test direction is parallel to the lamellar direction), and its wear rate is 2.96 × 10⁻⁶. -6 mm 3 / (N·m) (the grinding material is silicon nitride balls, and the pressure is 60N), which is 10%, 22%, and 10% higher than that of layered tungsten-copper composites prepared with tungsten foil, respectively. It is also significantly higher than coarse-grained tungsten-copper and uniform nanostructured tungsten-copper composites of the same composition. Relevant comparisons are as follows. Figure 2 and Figure 3 As shown.

[0029] Example 2

[0030] (a) Nano W-20Cu powder was prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material bulk with uniform nanocrystalline structure was prepared by rapid sintering technology (A);

[0031] (b) The uniform nanocrystalline W-20Cu composite material (A) was cut into a 200-micrometer-thick sheet (A foil, 20 mm in diameter) using wire cutting. At the same time, a 100-micrometer-thick pure copper sheet was cut into a sheet with the same diameter as A foil (B foil, 20 mm in diameter) using wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides from their surfaces.

[0032] (c) Alternately stack foil A and foil B (11 layers of foil A, 10 layers of foil B, the specific number can be adjusted as needed), place them in a mold, and perform rapid sintering at 900 degrees Celsius and 50 MPa for 10 minutes to prepare the (W-20Cu) / Cu layered heterostructure tungsten-copper composite material. Its SEM morphology is as follows: Figure 4 As shown.

[0033] Test results show that its compressive strength reaches 800 MPa (according to GB / T 228.1, the pressure direction is parallel to the lamellar direction), its electrical conductivity is 47.6% IACS (test direction is parallel to the lamellar direction), and its wear rate is 3.1 × 10⁻⁶. -6 mm 3 / (N·m) (The grinding material is silicon nitride balls, and the pressure is 60N).

[0034] Example 3

[0035] (a) Nano W-20Cu powder and nano W-90Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-20Cu composite material bulk with uniform nanocrystalline structure (A) and W-90Cu composite material bulk with uniform nanocrystalline structure (B) were prepared by rapid sintering technology.

[0036] (b) The uniform nanocrystalline W-20Cu composite material (A) was cut into a 150-micrometer-thick sheet (A foil, 20 mm in diameter) using wire cutting. At the same time, the uniform nanocrystalline W-90Cu nanocomposite material (B) was cut into a 100-micrometer-thick sheet (B foil, 20 mm in diameter) using wire cutting. Then, the wire-cut A foil and B foil were cleaned sequentially with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides from their surfaces.

[0037] (c) Alternately stack foil A and foil B (12 layers of foil A, 11 layers of foil B, the specific layers can be adjusted as needed), place them in a mold, and perform rapid sintering at 900°C and 100MPa for 10 minutes to prepare a (W-20Cu) / (W-90Cu) layered heterostructure tungsten-copper composite material. Its SEM morphology is shown below. Figure 5 As shown.

[0038] Test results show that its compressive strength reaches 1380 MPa (according to GB / T 228.1, the pressure direction is parallel to the lamellar direction), its electrical conductivity is 55.1% IACS (test direction is parallel to the lamellar direction), and its wear rate is 4.1 × 10⁻⁶. -6 mm 3 / (N·m) (The grinding material is silicon nitride balls, and the pressure is 60N).

[0039] Example 4

[0040] (a) Nano W-30Cu powder and nano W-90Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-30Cu composite material bulk with uniform nanocrystalline structure (A) and W-90Cu composite material bulk with uniform nanocrystalline structure (B) were prepared by rapid sintering technology.

[0041] (b) The uniform nanocrystalline W-30Cu composite material (A) was cut into a 200-micrometer-thick sheet (A foil, 20 mm in diameter) by wire cutting. At the same time, the uniform nanocrystalline W-90Cu nanocomposite material (B) was cut into a 200-micrometer-thick sheet (B foil, 20 mm in diameter) by wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides on their surfaces.

[0042] (c) Alternately stack A foil and B foil (8 layers of A foil and 7 layers of B foil, the specific number can be adjusted as needed), place them in a mold, and perform rapid sintering at 800 degrees Celsius and 100 MPa for 60 minutes to prepare (W-30Cu) / (W-90Cu) layered heterostructure tungsten copper composite material.

[0043] Example 5

[0044] (a) Nano W-40Cu powder and nano W-70Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-40Cu composite material bulk with uniform nanocrystalline structure (A) and W-70Cu composite material bulk with uniform nanocrystalline structure (B) were prepared by rapid sintering technology.

[0045] (b) The W-40Cu composite material (A) with uniform nanocrystalline structure was cut into a 100-micrometer-thick sheet (A foil, 20 mm in diameter) by wire cutting. At the same time, the W-70Cu composite material (B) with uniform nanocrystalline structure was cut into a 100-micrometer-thick sheet (B foil, 20 mm in diameter) by wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides on their surfaces.

[0046] (c) Alternately stack A foil and B foil (15 layers of A foil and 14 layers of B foil, the specific number can be adjusted as needed), place them in a mold, and perform rapid sintering at 800 degrees Celsius and 50 MPa for 40 minutes to prepare (W-40Cu) / (W-70Cu) layered heterostructure tungsten copper composite material.

[0047] Example 6

[0048] (a) Nano W-30Cu powder and nano W-80Cu powder were prepared by freeze-drying hydrogen reduction technology, and then W-30Cu composite material bulk with uniform nanocrystalline structure (A) and W-80Cu composite material bulk with uniform nanocrystalline structure (B) were prepared by rapid sintering technology.

[0049] (b) The W-30Cu composite material (A) with uniform nanocrystalline structure was cut into a 300-micrometer-thick sheet (A foil, 20 mm in diameter) by wire cutting. At the same time, the W-80Cu composite material (B) with uniform nanocrystalline structure was cut into a 300-micrometer-thick sheet (B foil, 20 mm in diameter) by wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides on their surfaces.

[0050] (c) Stack A foil and B foil alternately (6 layers of A foil and 5 layers of B foil, the specific number can be adjusted as needed), place them in a mold, and sinter rapidly at 900 degrees Celsius and 150 MPa for 20 minutes to prepare (W-30Cu) / (W-80Cu) layered heterostructure tungsten copper composite material.

[0051] Example 7

[0052] (a) Nano W-10Cu powder was prepared by freeze-drying hydrogen reduction technology, and then W-10Cu composite material bulk with uniform nanocrystalline structure was prepared by rapid sintering technology (A).

[0053] (b) Using wire cutting, the W-10Cu composite material (A) with a uniform nanocrystalline structure was cut into a 400-micrometer-thick sheet (A foil, 20 mm in diameter). At the same time, a 200-micrometer-thick pure copper sheet was cut into the same diameter (B foil, 20 mm in diameter) using wire cutting. Then, the wire-cut A foil and B foil were cleaned in sequence with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water to remove oxides on their surfaces.

[0054] (c) Stack A foil and B foil alternately (5 layers of A foil and 4 layers of B foil, the specific number can be adjusted as needed), place them in a mold, and sinter rapidly at 900 degrees Celsius and 100 MPa for 20 minutes to prepare (W-10Cu) / Cu layered heterostructure tungsten copper composite material.

Claims

1. A method for preparing a layered heterostructure tungsten-copper composite material, characterized in that, Includes the following steps: (a) Using rapid sintering technology, high-tungsten-content tungsten-copper composite material A and low-tungsten-content tungsten-copper composite material B with ultrafine or nanocrystalline structures were prepared by sintering respectively. (b) Two tungsten copper composite materials were cut into thin sheets of the same size using wire cutting, and named foil A and foil B respectively. Foil A and foil B were then cleaned with sodium hydroxide solution, dilute hydrochloric acid solution and deionized water in sequence to remove oxides from their surfaces. (c) Alternately stack foil A and foil B, place them in a mold, and sinter them rapidly under a certain temperature and pressure to obtain the layered heterostructure tungsten copper composite material. In step (a), the tungsten phase grain size in the ultrafine or nanocrystalline tungsten-copper composite material is 50-500 nanometers, the copper content of the tungsten-copper composite material corresponding to A is 10%-40% by mass, and the copper content of the tungsten-copper composite material corresponding to B is greater than or equal to 60% and less than 100% by mass. In step (b), the thickness of the tungsten-copper composite material sheet cut by wire cutting is 50-500 micrometers; In step (c), the sintering temperature is 700-950 degrees Celsius, the pressure is 50-200 MPa, and the sintering time is 10-60 minutes. The prepared layered heterostructure tungsten-copper composite material exhibits a non-uniform layered structure with alternating tungsten-rich and tungsten-poor layers, and the grain size of the tungsten phase is between 50-500 nanometers.

2. A layered heterostructure tungsten-copper composite material prepared according to the method of claim 1, having a non-uniform layered structure with alternating tungsten-rich and tungsten-poor layers.

Citation Information

Patent Citations

  • Tungsten / copper layered composite material, preparation method and application thereof

    CN114193856A

  • Preparation method of tungsten / copper layered composite material for thermonuclear fusion

    CN114701237A

  • Low-temperature rapid preparing method for high-density nanocrystalline tungsten copper base block composite materials

    CN109852861A

  • High-strength and high-conductivity ultra-fine grain tungsten-copper composite material and preparation method

    CN114086013A

  • Preparation method of tungsten-copper composite material

    CN117500247A